A. (3w-1) = (3w)
B (3w-1) = -(3w)
C. -(3w-1) = (3w)
D. -3(w-1) = -(3w)
A and D are the same, use A
B and C are the same, use B
3w-1 = 3w
0 * w = 1 no solution possible
3 w - 1 = - 3 w
6 w = 1
w = 1/6
Algebra Problem - I can't fugure out how to solve (6-3w)(-w to the second power...
Algerbra 1 - What is the simplified form of the expression? -(8d - 3w) A. 8d - ...
pre algebra - how would you solve and check the answer, back to the original ...
Algebra - -9+3w/11 divided by 25w-75/121 Do I need a Common denominator? Would ...
Math - Factor Completely: I am really confused on how to start it. 12q^5w^2-36q^...
mat117/algebra - Rewrite the middle term as the sumof two terms and then factor ...
ALGEBRA - I need help finding the LCM of (8+3w) (64-9w^2) (8-3w)
algebra 1 - simplify 3w-12/3w
Math - Using the formula r = d/t, where d is the distance in miles, r is the ...
math - 2/3w+2=5/3w w=